Dynamical probe of the pseudo Jahn-Teller effect in one-dimensional confined fermions - A. Becker; G. M. Koutentakis; P. Schmelcher (Physical Review Research)
We investigate the real-time dynamics of a quenched quantum impurity immersed in a one-dimensional ultracold Fermi gas, focusing on the breakdown of the adiabatic Born-Oppenheimer approximation due to nonadiabatic effects. Despite a sizable impurity-bath mass imbalance, increasing interactions induce strong nonadiabatic couplings, disrupting adiabatic motion and enabling population transfer between the adiabatic potential energy curves. These transitions are governed by conical intersections arising from the pseudo Jahn-Teller effect, dynamically shaping the impurity's motion through the bath. Using ab initio simulations via the multilayer multiconfiguration time-dependent Hartree method and a multichannel Born-Oppenheimer framework, we track the impurity's evolution and directly prove the dynamical manifestation of the pseudo Jahn-Teller effect. We analyze two key scenarios: (i) a small initial shift, where a single avoided crossing drives transitions, and (ii) a large shift, where multiple avoided crossings lead to enhanced nonadiabaticity, self-trapping, and energy redistribution. Our findings establish ultracold fermionic few-body systems as tunable platforms for studying nonadiabatic quantum dynamics, opening new avenues for controlled impurity transport in strongly correlated environments.